Whole Exome Sequencing Reveals Genetic Variants in HLA Class II Genes Associated With Transplant-free Survival of Indeterminate Acute Liver Failure. Issue 7 (2nd July 2022) - Liao, Tsung-Jen; Pan, Bohu; Hong, Huixiao; Hayashi, Paul; Rule, Jody A.; Ganger, Daniel; Lee, William M.; Rakela, Jorge; Chen, Minjun
Abstract : INTRODUCTION: Indeterminate acute liver failure (IND-ALF) is a rare clinical syndrome with a high mortality rate. Lacking a known etiology makes rapid evaluation and treatment difficult, with liver transplantation often considered as the only therapeutic option. Our aim was to identify genetic variants from whole exome sequencing data that might be associated with IND-ALF clinical outcomes. METHODS: Bioinformatics analysis was performed on whole exome sequencing data for 22 patients with IND-ALF. A 2-tier approach was used to identify significant single-nucleotide polymorphisms (SNPs) associated with IND-ALF clinical outcomes. Tier 1 identified the SNPs with a higher relative risk in the IND-ALF population compared with those identified in control populations. Tier 2 determined the SNPs connected to transplant-free survival and associated with model for end-stage liver disease serum sodium and Acute Liver Failure Study Group prognostic scores. RESULTS: Thirty-one SNPs were found associated with a higher relative risk in the IND-ALF population compared with those in controls, of which 11 belong to the human leukocyte antigen (HLA) class II genes but none for the class I. Further analysis showed that 5 SNPs: rs796202376, rs139189937, and rs113473719 of HLA-DRB5; rs9272712 of HLA-DQA1; and rs747397929 of IDO1 were associated with a higher probability of IND-ALF transplant-free survival. Using 3 selected SNPs, a model for the polygenic risk score was developed to predict IND-ALF prognoses, which are comparable with those by model for end-stage liver disease serum sodium and Acute Liver Failure Study Group prognostic scores. DISCUSSION: Certain gene variants in HLA-DRB5, HLA-DQA1, and IDO1 were found associated with IND-ALF transplant-free survival. Once validated, these identified SNPs may help elucidate the mechanism of IND-ALF and assist in its diagnosis and management.